Azithromycin-liposomes as a novel approach for localized therapy of cervicovaginal bacterial infections - Vanić, Željka (Int J Nanomedicine, 2019)
BACKGROUND: Efficient localized cervicovaginal antibacterial therapy, enabling the delivery of antibiotic to the site of action at lower doses while escaping systemic drug effects and reducing the risk of developing microbial resistance, is attracting considerable attention. Liposomes have been shown to allow sustained drug release into vaginal mucosa and improve delivery of antibiotics to bacterial cells and biofilms. Azithromycin (AZI), a potent broad-spectrum macrolide antibiotic, has not yet been investigated for localized therapy of cervicovaginal infections, although it is administered orally for the treatment of sexually transmitted diseases. Encapsulation of AZI in liposomes could improve its solubility, antibacterial activity, and allow the prolonged drug release in the cervicovaginal tissue, while avoiding systemic side effects. PURPOSE: The objective of this study was to develop AZI-liposomes and explore their potentials for treating cervicovaginal infections. METHODS: AZI-liposomes that differed in bilayer elasticity/rigidity and surface charge were prepared and evaluated under simulated cervicovaginal conditions to yield optimized liposomes, which were assessed for antibacterial activity against several planktonic and biofilm-forming Escherichia coli strains and intracellular Chlamydia trachomatis, ex vivo AZI vaginal deposition/penetration, and in vitro cytotoxicity toward cervical cells. RESULTS: Negatively charged liposomes with rigid bilayers (CL-3), propylene glycol liposomes (PGL-2) and deformable propylene glycol liposomes (DPGL-2) were efficient against planktonic E. coli ATCC 700928 and K-12. CL-3 was superior for preventing the formation of E. coli ATCC 700928 and K-12 biofilms, with IC(50) values (concentrations that inhibit biofilm viability by 50%) up to 8-fold lower than those of the control (free AZI). DPGL-2 was the most promising for eradication of already formed E. coli biofilms and for treating C. trachomatis infections. All AZI-liposomes were biocompatible with cervical cells and improved localization of the drug inside vaginal tissue compared with the control. CONCLUSION: The performed studies confirm the potentials of AZI-liposomes for localized cervicovaginal therapy.